Influence of cultivar and cutting date on the fatty acid composition of forage crops for grazing beef production in Argentina - García, Teresa Pilar (2015)
The fatty acid composition and total lipids of various forage crops at different cutting dates and seasons, which are used in forage grazing beef production in Argentina, were determined. Three experiments were carried out at the Agricultural Experimental Station of INTA, Anguil, La Pampa, Argentina Samples of alfalfa from three different cultivars with different dormancy groups (G4‐5, G6‐7 and G8‐9) and samples of ryegrasses Bill, Florida and Queue, wheats Charrua and Guapo, and triticale Don Santiago cultivars were taken at different cutting dates and analysed for total lipids and fatty acid composition. Significant differences on the fatty acid composition, the ratios 18:3n‐3/18:2n‐6 and polyunsaturated fatty acids (PUFA) due to cultivar, cutting date and season were found. Taking into account the importance of 18:2n‐6 and 18:3n‐3 fatty acids as substrates for the conjugated isomers of 18:2n‐6 (CLA) and n‐3 PUFA concentrations in beef, the fatty acid composition of forages needs to be considered in forage grazing beef production systems. Data variation in both total lipids and individual fatty acid proportions in forages should be taken into account to establish the potential to cultivate crops for a higher content of n‐3 PUFA and hence the opportunity to deliver more n‐3 PUFA and CLA into beef.